Lifeskill-Based Interactive Multimedia Training and Assistance to Improve Education Services at SDN Gondang Wetan 1 Pasuruan - Ludfi Arya Wardana; Rofikha Nuriyanti; Farah Sayu Athilah; Mala Sastia Novita Sari; Tri Utami Prastyaningsih (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Community service is carried out to the teachers of SDN Gondangwetan 1 Pasuruan in the form of lifeskill-based interactive multimedia training and mentoring. The purpose of this service is to improve the understanding and skills of teachers in creating interactive multimedia based on life skills to improve educational services. The implementation method is in the form of activity planning, activity implementation, implementation techniques, monitoring and evaluation and recognition. The results and discussion of this service are an enthusiastic increase in the understanding process and interactive multimedia products based on life skills so as to improve educational services at SDN Gondangwetan 1 Pasuruan.